Sacroiliac dysfunction - Diagnosis and treatment approaches: a clinical study - Martins, Maria Joana da Gama Lobo Paula (2022)
The present work entails all the activities performed and assisted during the externships at Lingehoeve Diergeneeskunde, under the guidance of Peter Wiemer, and at Paardenkliniek Venlo, under the guidance of Liana Peters. The first part of this report partakes a descriptive statistic of the caseload. It is divided into different areas of the equine medicine and a small theoretical background is included for contextualization of a representative case chosen for each area of practice. The second part consists of a monography, involving a bibliographic revision of sacroiliac dysfunction associated with poor performance in sports horses, followed by a clinical study on the diagnostic and treatment approaches to this condition, based on the caseload assisted during the externship at De Lingehoeve, to provide a synthesis of the signs associated with this condition and assess the validity and success of the treatments instated; Disfunção Sacroilíaca – Abordagens diagnósticas e terapêuticas: um estudo clínico Resumo: Este trabalho relata as atividades realizadas e assistidas ao longo dos estágios curriculares realizados no hospital De Lingehoeve Diergeneeskunde, sob orientação do Dr. Peter Wiemer, e na clínica Paardenkliniek Venlo, sob orientação da Dr.ª. Liana Peters. A primeira parte deste relatório apresenta uma estatística descritiva da casuística. Foi incluído um breve resumo teórico para cada área da medicina de equinos, para contextualização dos casos selecionados considerados relevantes para cada uma destas áreas. A segunda parte é composta por uma monografia de revisão bibliográfica acerca da disfunção sacroilíaca associada com perda de performance em cavalos de desporto, seguida um estudo clínico das abordagens diagnósticas e de tratamento desta condição, tendo como base de dados a casuística acompanhada durante o estágio em De Lingehoeve, e que pretende, para além de providenciar uma síntese dos sinais clínicos e imagiológicos associados a esta condição, avaliar a validade e sucesso dos tratamentos instituídos.